2019
DOI: 10.20960/nh.02607
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia de sarcopenia y características de los sarcopénicos en pacientes mayores de 80 años ingresados por fractura de cadera

Abstract: Background: Choosing the method of nutritional assessment is essential for proper follow-up of the nutritional status of patients undergoing liver transplantation. Objectives: Evaluate and compare the nutritional status of cirrhotic patients before and after liver transplantation over a year by different methods of nutritional assessment. Methods: Patients undergoing liver transplantation were assessed in five phases: pre-transplant, 1, 3, 6 and 12 months after transplantation at the hospital Santa Casa de Mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
4
0
2
Order By: Relevance
“…Baseline characteristics of the 150 participants are listed in Table , and we previously published these results in detail elsewhere . In brief, mean age was 87.6 ± 4.9 years, and 78.7% were women.…”
Section: Resultsmentioning
confidence: 99%
“…Baseline characteristics of the 150 participants are listed in Table , and we previously published these results in detail elsewhere . In brief, mean age was 87.6 ± 4.9 years, and 78.7% were women.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, in Spain, Cervera-Días et al identified the highest percentage of sarcopenia among 186 patients hospitalized for hip fracture, 76.9% (mean age 86.2 years) [ 37 ]. On the other hand, in the study of Sánchez-Castellano et al, the sarcopenia prevalence among 150 patients (mean age 87.6 years) was estimated to be between 11.5 and 34.9% according to different equations used to estimate muscle mass (bioimpedance, using two different cut-off points, Janssen and Masanés) [ 10 ]. González-Montalvo et al detected 17.1% sarcopenics among 479 acute hip fracture patients (mean age 85.3 years) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The latest projections from the Spanish National Statistics Institute (INE) indicate that in 2050, 31.4% of the population will be aged over 65 years and 11.6% will be octogenarians [ 9 ]. Recent estimates also show that the prevalence of sarcopenia in older hip fracture patients in Spain ranged from 21 to 74% in men and 12 to 68% in women, depending on its definition and diagnosis [ 10 ]. Sarcopenia and hip fracture are considered major public health problems in the geriatric population requiring substantial costs for their management [ 8 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study exploring neuromuscular, peripheral pro-inflammatory, and oxidative stress molecules as potential biomarkers associated with sarcopenia in old-aged people with hip fracture only found differences in peripheral TNF-α levels and catalase activity. Probably, TNF-α and catalase are markers of an early inflammatory reaction that is impaired in subjects with sarcopenia [12].…”
Section: Inflammatory Markers In Sarcopeniamentioning
confidence: 99%